Undergraduate Student Award in Environmental Chemistry, Division of Environmental Chemistry - Antoniou, Maria G. (My University, 2026)
My undergraduate advisee in research Nikoletta I. Tsiarta: Undergraduate Student Award in Environmental Chemistry, Division of Environmental Chemistry, American Chemical Society, April 2015.
Keywords: Sciences